Health Law as A Pillar of The Welfare State: Theory, Practice and The Future - Andika Rafa Hendrawan; Bayu Arif Hi Ahdar; Samsul Huda; Aris Prio Agus Santoso (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Health is a fundamental right guaranteed by the constitution and a key pillar in the development of a welfare state. Health law serves as a normative instrument that regulates the provision of services, protects patient rights, regulates the obligations of medical personnel, and ensures the accountability of healthcare institutions. However, the reality in Indonesia demonstrates a significant gap between normative construction and empirical implementation. Key challenges include disparities in access to services, a deficit in National Health Insurance funding, an unequal distribution of healthcare workers, and regulatory fragmentation. The COVID-19 pandemic further emphasizes the importance of health law not only as an administrative tool but also as a mechanism for state resilience in the face of public health crises. This study aims to analyze health law in three dimensions: theoretical, practical, and prospective. Theoretically, health law affirms the state's responsibility to guarantee the right to health as part of a welfare state. Practically, it reflects the effectiveness of public policy and healthcare system governance. Prospectively, health law must adapt to the digitalization of services, the protection of patient data, and the global commitment to universal health coverage. Thus, health law serves not only as a regulatory framework but also as a strategic foundation that unites human rights protection, policy effectiveness, and social justice in building a sustainable welfare state.